Inteligência de segurança pública no estado do Amazonas: análise dos indicadores criminais relacionados aos conflitos agrários em ramais do sul de Lábrea - Andrade, Cleaci Gertrudes De (2014)
Public Security Intelligence in the State of Amazonas: analysis of criminal indicators related to agrarian conflicts in Southern Lábrea side roads" is a proposed study aimed to contextualize the history of conflicts in Southern Lábrea City, identify and select the data related to criminal cases from 2010 to 2012, propose suggestions on how Public Security Intelligence could collaborate to this land conflicts area, interpret the data of the field research, the number of people surveyed, the place they live in and analyze the answers of the survey that resulted in graphics. It also aimed to explain particular characteristics of the side roads “Mendes Junior”, “do Boi” and “Jequitibá”, focal area of this study, the situation of the regulation of existing settlements in these side roads with INCRA, comment the agrarian conflicts and Public Safety organs’ actions, social movements and legal conflicts, some violent incidents in the countryside, identify the people involved in these land conflicts and to propose suggestions to the authorities about the conclusions of the research. The methodology used in this study consisted of bibliographical and field researches, which have enabled a more consistent analysis of survey data.